The Pennybridge pioneers: understanding internal stakeholder perceptions of body-worn camera implementation - Koen, Marthinus C. (Journal of crime and justice, 2023)
Since body-worn cameras (BWCs) were catapulted into mainstream discourse, they have diffused rapidly across police agencies in the United States. Research followed swiftly, providing a wealth of information about how the police and citizens make sense of these technologies. Moreover, we have learned how these technologies have impacted important policing outcomes, such as citizen complaints and the use of coercive force during citizen encounters. However, despite the growing body of research, very little is known about how police stakeholders make sense of the implementation of BWCs and about their decision-making throughout the implementation process. Therefore, this research examines the decision to implement BWCs in one mid-sized municipal police department in the United States through the lens of Rogers (2003) Diffusion of Innovations theoretical framework. We rely on semi-structured interviews and observations with 17 stakeholders to address this question. Our findings show that BWC technology generally posed little uncertainty for stakeholders in terms of what it could offer conceptually. However, because the agency was an early adopter, decision-makers were confronted with significant uncertainty about practical matters such as the financial and logistical costs of implementing the technology, in addition to policy creation. These findings have important implications for scholars and practitioners.